2015
DOI: 10.1111/jvim.12481
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Magnetic Resonance Imaging, and Histopathologic Findings in 6 Dogs with Surgically resected Extraparenchymal Spinal Cord Hematomas

Abstract: BackgroundExtraparenchymal spinal cord hematoma has been described in veterinary medicine in association with neoplasia, intervertebral disk disease, and snake envenomation. There are rare reports of spontaneous extraparenchymal spinal cord hematoma formation with no known cause in human medicine. Multiple cases of spontaneous extraparenchymal spinal cord hematoma have not been described previously in veterinary medicine.ObjectivesTo describe the signalment, clinical findings, magnetic resonance imaging (MRI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 31 publications
5
28
0
1
Order By: Relevance
“…10 Intraspinal hemorrhage has a characteristic appearance on MRI depending on its age, as reported by Braun et al 16 In the dog reported here, the presence of both T1 and T2 hyperintensity with the absence of susceptibility artifact on the T2*-weighted images and the lack of suppression on FLAIR-weighted images is most compatible with ISH in the late subacute phase, based upon human reports, 16 and is similar to prior descriptions in dogs. 15 The clinical progression described in the dog reported here, however, was more consistent with an acute process. There are additional descriptions of ISH in humans where both T1 and T2 hyperintensity are reported within the peracute and acute time frames, 17 which is consistent with the dog reported here.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…10 Intraspinal hemorrhage has a characteristic appearance on MRI depending on its age, as reported by Braun et al 16 In the dog reported here, the presence of both T1 and T2 hyperintensity with the absence of susceptibility artifact on the T2*-weighted images and the lack of suppression on FLAIR-weighted images is most compatible with ISH in the late subacute phase, based upon human reports, 16 and is similar to prior descriptions in dogs. 15 The clinical progression described in the dog reported here, however, was more consistent with an acute process. There are additional descriptions of ISH in humans where both T1 and T2 hyperintensity are reported within the peracute and acute time frames, 17 which is consistent with the dog reported here.…”
Section: Discussionsupporting
confidence: 50%
“…There are additional descriptions of ISH in humans where both T1 and T2 hyperintensity are reported within the peracute and acute time frames, which is consistent with the dog reported here. The presumptive ISH in this case demonstrated peripheral contrast enhancement, which has previously been reported in humans and dogs . The variability of MRI findings in people with ISH and the lack of consistency among the limited reports in the veterinary literature, combined with the presence of severe thrombocytopenia and the absence of any other findings, led the authors to consider ISH secondary to ITP as the most likely diagnosis in this case .…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…estudaram o hematoma espinhal extra parenquimatoso espontâneo em cães e um dos métodos diagnósticos usados foi a RM, eles realizaram a RM em 6 seis cães com esse tipo de hematoma utilizando as sequências T2, T1 pré-contraste e T1 pós-contraste. Os autores observaram que os hematomas de todos os cães ficaram com alta intensidade de sinal nas imagens de T2, nas imagens de T1 sem o contraste os hematomas ficaram com baixa intensidade de sinal em 4 de 6 cães, com média intensidade de sinal em 1 cão e com alta intensidade de sinal na periferia do hematoma em 1 cão em T1 com contraste, a hemorragia ficou contrastada em apenas 1 dos seis cães (80) .…”
Section: Avaliação Por Imagemunclassified